Modulation of T Cell Metabolism and Function through Calcium Signaling - Fracchia, Kelley M.; Pai, Christine; Walsh, Craig M. (Frontiers in Immunology, 2013)
As a vital second messenger in the activation of lymphocytes, the divalent cation Ca2+ plays numerous roles in adaptive immune responses. Importantly, Ca2+ signaling is essential for T cell activation, tolerance of self-antigens, and homeostasis. Supporting the essential role of Ca2+ signaling in T cell biology, the Ca2+ regulated protein phosphatase calcineurin is a key target of pharmacologic inhibition for preventing allograft rejection and for autoimmune therapy. Recent studies have highlighted the unique role of Stim1 and Orai1/2 proteins in the regulation of store operated/calcium release activated calcium (CRAC) channels in the context of T cells. While Ca2+ is known to modulate T cell activation via effects on calcineurin and its target, nuclear factor of activated T cells (NFAT), this second messenger also regulates other pathways, including protein kinase C (PKC), calmodulin kinases (CamKs) and cytoskeletal proteins. Ca2+ also modulates the unique metabolic changes that occur during in distinct T cell stages and subsets. Herein, we discuss the means by which Ca2+ mobilization modulates cellular metabolism following T cell receptor ligation. Further, we highlight the crosstalk between mitochondrial metabolism, reactive oxygen species (ROS) generation and CRAC channel activity. As a target of mitochondrial ROS and Ca2+ regulation, we describe the involvement of the serine/threonine kinase DRAK2 in the context of these processes. Given the important roles for Ca2+ dependent signaling and cellular metabolism in adaptive immune responses, the crosstalk between these pathways is likely to be important for the regulation of T cell activation, tolerance and homeostasis.